Epistemological Obstacles in Geometry within the Context of Gen Z Digital Culture: Hambatan Epistemologis Geometri dalam Konteks Budaya Digital Gen Z - Hidayat, Abas (jsd: Journal of Society and Development, 2025)
Geometry demands profound deductive-axiomatic reasoning; however, Generation Z has grown up within a digital culture that prioritizes instant visual information. This study aims to analyze the epistemological obstacles in geometry encountered by Gen Z students resulting from the influence of these digital culture characteristics. This research employs a qualitative descriptive method involving 250 high school students born between 2007 and 2010 in the City and Regency of Cirebon. Data were collected through diagnostic tests and in-depth interviews, then analyzed using Brousseau’s theoretical framework. The results identify a shift in the forms of obstacles: first, visual-perceptual obstacles, where students validate geometric truth solely based on visual appearance, adhering to a "what looks right is right" mindset while disregarding deductive logic. Second, instrumental obstacles, characterized by a dependence on instant problem-solving applications, which hinders the construction of mental concepts. Digital culture is shown to facilitate an "illusion of understanding" and reduce student resilience in engaging with lengthy mathematical proofs. This study contributes as a foundation for designing didactic strategies to mitigate the negative effects of the culture of instant thinking, emphasizing the importance of transitioning from digital visualization toward rigorous analytical proof.